Effects of post-activation performance enhancement in kayak sprint competition within same day - Phongsri, K.; Khamros, W.; Peepathum, P.; Senakham, N.; Sriramatr, S.; Senakham, T. (SportMont, 2024)
The purpose of this study was to determine the post-activation performance enhancement in kayak sprint competitive simulation 2 times (S1 and S2) within the same day. This study was a crossover design, ten kayak sprint paddles national team performed different activations. All participants will be randomized crossover trials, get three interventions consisting of the Resistance program (2 x 4 x 80%1RM x Bench press and Bench row), Maximum sprint paddle (Ergometer all-out 2 x 10-sec x rest interval 2 min) and Control group (CON; Individual activity condition) followed 3-minute test (3MT). Maximum power, power average, stroke per minute, total distance, percentage of heart rate, and blood lactate concentration were recorded during the simulation competition. The main effect of the analysis showed that maximum power of the Resistance program was higher than the Control group in S1. The average power and total distance of the Resistance program in S2 were lower than in S1. Blood lactate concentration of the Resistance program and Maximum sprint paddle was higher than the Control group after the intervention, before the 3MT period, and remained rise until after 3MT, especially in S2. Also, blood lactate concentration before the intervention of the Resistance program in S2 was higher than in S1. The preconditioning by using the resistance or maximum sprint paddle improves maximum power only the first competition of the day. It seems that the resistance program leads to accumulated blood lactate concentration, and may decrease performance in the second competition of the day.